Ghost train. - Young, RobertJ C (Postcolonial Studies, 2007)
The time, 1932: a spectre is haunting Europe, and far beyond. Usurping the night, it abstracts the unwary and distracts them into taking an inphantomising ride from Camden Street Station at the Trocadero Cinema, Liverpool. This thing, subaltern and spectral, subjects its passengers to ghostly memories and ghastly premonitions.